Characteristics of Boron Decorated TiO2 Nanoparticles for Dye-Sensitized Solar Cell Photoanode - Ching-Yuan Ho; J. K. Lin; Hong-Wen Wang (International Journal of Photoenergy)
Different boron weight percents on mixed-phase (anatase and rutile) TiO2 nanoparticles were synthesized to investigate structure morphology, defect states, luminescence properties, and energy conversion. The measured results indicate that boron doping of TiO2 both increases the crystallite size and rutile-phase percent in an anatase matrix. Decreasing the band gap by boron doping can extend the absorption to the visible region, while undoped TiO2 exhibits high UV absorption. Oxygen vacancy defects generated by boron ions reduce Ti+4 and affect electron transport in dye-sensitized solar cells. Excess electrons originating from the oxygen vacancies of doped TiO2 downward shift in the conduction band edge and prompt the transfer of photoelectrons from the conduction band of the rutile phase to the lower energy anatase trapping sites; they then separate charges to enhance the photocurrent and Jsc. Although the resistance of the electron recombination (Rk) between doped TiO2 photoanode and the electrolyte for the doped TiO2 sample is lower, a longer electron lifetime (τ) of 19.7 ms with a higher electron density (ns) of 2.1 × 1018 cm−3 contributes to high solar conversion efficiency.